2017
DOI: 10.1055/s-0037-1599786
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Cerebrospinal Fluid Diversion (Shunt) Catheters: A Pictorial Essay

Abstract: Ventriculoperitoneal shunt catheters are very commonly used for hydrocephalus of varying etiologies in infancy to childhood to bypass the obstruction. Few people are aware of their complications, such as infection, obstruction, malfunctioning, displacements, fluid collections, disconnections, and entry into various intra-abdominal organs. These complications and related literature and images are presented in this essay. In some cases, a radiologist can be of use to a neurosurgeon to alert what complication a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The studies on shunt dysfunctions are consistent in the general incidence of failure after the initial insertion [12]. Most present approximately 40% in 1 year and 50% in the second year after insertion.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The studies on shunt dysfunctions are consistent in the general incidence of failure after the initial insertion [12]. Most present approximately 40% in 1 year and 50% in the second year after insertion.…”
Section: Discussionsupporting
confidence: 57%
“…Long term follow-up data from the Shunt Design Trial demonstrated an overall shunt survival of 41% over 4 years. In another study up to 50% in first year of life and up to 4 to 5% per year thereafter, and as high as 81% after 12 years [12].…”
Section: Discussionmentioning
confidence: 83%
“…Extrusion of the peritoneal catheter through the abdominal wall is rare [1]. While the proximal portion of the catheter can migrate into the blood [5], it can cause distal complications such as: extrusion of the catheter via umbilical scar [6], abdominal wall, vagina, urethra and anus [9].…”
Section: Etiologymentioning
confidence: 99%
“…Ventriculoperitoneal shunt (VPS) is a neurosurgical intervention indicated for the control and treatment of hydrocephalus [1]. The most common complications of this procedure are: erosion of the skin at the valve site, edema along the catheter path [2], infections [3], malfunction mechanical system [4], disconnection and subdural hematoma [5]. Abdominal complications resulting from the distal catheter are: obstruction of catheter [2], fracture and/or disconnection [5], migration [6], abscess [3], abdominal wall cyst [4], perforations in intestine [3]; bladder [5]; and scrotum [7], and extrusion of the catheter through the vagina [8]; anus [4]; lumbar; and cervical region [6].…”
Section: Introductionmentioning
confidence: 99%
“…8 Other complication includes catheter migration, bowel perforation, pseudocyst formation, subdural hematoma formation, hemiplegia, etc. 9,10 We undertook a prospective data analysis of all the cases of VP shunt surgery over a period of about one and half year done in the Department of Neurosurgery, Institute of Medical Sciences, Banaras Hindu University, Varanasi, which is a tertiary care center. This single hospital-based epidemiological study, being one of its kind, will hopefully serve the purpose of analyzing various indication and complications of VP shunt surgery in the given population.…”
Section: Introductionmentioning
confidence: 99%